Analysis of the Influence of Real Earnings Management, Income Smoothing and Tenure Audit on Cofficient Earnings Response with Intellectual Capital Disclosure as Moderating Variables - Ma'rifah, Julia Dewi; Amarta, Zain; Sany, Nukhbah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to re-examine the factors that influence and moderate the earnings response coefficient in manufacturing companies. These variables are Real Earnings Management, Income Smoothing, Audit Tenure, and Intellectual Capital Disclosure. The sample of this study consists of 68 manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2017 and selected by the purposive sampling method. This study uses moderated regression analysis. The results of this study shows that real earnings management has no negative influence to earnings response coefficient. Reversly, income smoothing has a negative influence to earnings response coefficient, audit tenure has no influence to earnings response coefficient while intellectual capital disclosure has no positive influence to earnings response coefficient. In other that, Intellectual capital disclosure does not weaken the negative influence of real earnings management and audit tenure to earnings response coefficient. However, Intellectual capital disclosure is proven to weaken the negative influence of income smoothing to earnings response coefficient.